Zinc Absorption and Endogenous Fecal Zinc Losses in Bangladeshi Toddlers at Risk for Environmental Enteric Dysfunction. Issue 6 (June 2019) - Mondal, Prasenjit; Long, Julie M.; Westcott, Jamie E.; Islam, M. Munirul; Ahmed, Mondar; Mahfuz, Mustafa; Ahmed, Tahmeed; Miller, Leland V.; Krebs, Nancy F.
ABSTRACT: Objectives: Environmental enteric dysfunction (EED) impairs zinc absorption from food, and zinc deficiency may contribute to the poor growth associated with EED. We examined zinc absorption from a standardized aqueous zinc dose, and habitual daily endogenous fecal zinc excretion (EFZ) and compared these outcomes between children grouped by the lactulose to mannitol ratio (L:M). Methods: Bangladeshi toddlers (18–24 months) with low (<0.09) and high (≥0.09) L:M were administered isotope-labeled 3 mg aqueous zinc in the fasted state. Fractional absorption of zinc (FAZ) and EFZ were measured by dual stable isotope tracer method and an isotope dilution method, respectively. Secondary aims included examining relationships of biomarkers of systemic and intestinal inflammation and gut function with FAZ and EFZ. Results: Forty children completed the study; nearly all had evidence of EED. No differences in zinc homeostasis measurements (mean ± SD) were observed between high and low L:M groups: FAZ was 0.38 ± 0.19 and 0.31 ± 0.19, respectively; both figures were within estimated reference range. Means of EFZ were 0.73 ± 0.27 and 0.76 ± 0.20 mg/day for high and low L:M, respectively, and were 10% to 15% above estimated reference range. Regression analyses indicated that biomarkers of systemic inflammation were directly associated with increasing FAZ, consistent with increased gut permeability. Biomarkers of intestinal inflammation were negatively associated with EFZ, consistent with low-zinc intake and chronic deficiency. Conclusions: In these children at risk of EED, endogenous zinc losses were not markedly increased. Results suggest that efforts to improve zinc status in EED should focus on substantially improving zinc intakes. Abstract : Supplemental Digital Content is available in the text